Rancangan Program Pengembangan SDM Stratejik Berbasis Kompetensi untuk Level Manajer di PT XYZ - Prabowo, Chandra Wihardito; Saragih, Eva Hotnaidah (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
PT XYZ, a company in outsourcing business, is in the midst of business model change. This change demands two things from the employees. First, because of the increasing complexity of the intended business process, companies need to improve their employees' capabilities. Second, for the process of change to work well and quickly employees need to be in tune with the core competencies of the company. This thesis focuses on achieving that second demand through employee development strategies and programs at the manager level. Managers have a role as a bridge between top management and staff. This unique position makes the manager role as a lever in the internalization of core competencies. The success of PT XYZ instilling core competencies in managers will determine the success of internalizing core competencies across the company. The success of such internalization will determine the success of business model change which will be the future of the company. This will be the foundation of PT XYZ in doing evolution. This thesis produces the design of the strategic scope and program scope of human resource development based on core competency. The strategic scope ensures human resource development will align with and support the corporate strategy. The program scope designs appropriate development activities to build core competencies, develop ways to evaluate them, and ensure managers can apply these core competencies in their jobs.